Pengaruh Perendaman Telur dengan Larutan Hidrogen Peroksida terhadap Penurunan Bobot, Haugh Unit dan Indeks Putih Telur Itik Konsumsi Selama Penyimpanan pada Suhu Ruang - Widjaya, Nilawati (Universitas Sebelas Maret (UNS), 2013)
This objective of the research was to know the effect of soaking with hydrogenperoxide on weight reduction, haugh unit and albumen index of duck eggs during storage at room temperature. The research was designed as Completely Randomize Design (CRD) wtih four treatments and six replicates each. The treatments were: soaking with aquades, soaking with 1, 2, and 3% of hydrogen The data were analyzed by analysis of variance and continued with Duncan Multiple Range Test. The results indicated that soaking with hydrogen peroxyde influended the egg weight, Haugh Unit and albumen index at chamber temperature during the storage. Soaking with 1% hydrogen peroxide showed the best results compared with the other treatments.Key words: soaking, hydrogen peroxide, weight decrease, haugh unit, albumen index